Dynamics of thermally induced assembly of Au nanoislands from a thin Au layer on Ge(001). Issue 30 (24th June 2016) - Nikiel, M.; Jany, B. R.; Wrana, D.; Szajna, K.; Janas, A.; Kozubski, R.; Krok, F.
Abstract : A systematic study of the thermally induced self-organization of a 6 ML Au layer on the Ge(001) surface by SEM, TEM and AFM techniques. Abstract : The dynamics of morphology changes upon post-deposition annealing of a thin film of 6 ML Au deposited on a (2 × 1) reconstructed Ge(001) surface was studied in a systematic way by scanning electron and atomic force microscopy. It has been found that annealing of the initial, continuous Au layer leads to the development of nanoislands which are crystalline and epitaxial to the Ge(001) substrate surface. The nanoislands formed at annealing temperatures lower than the bulk eutectic temperature for the Au–Ge system (634 K) are rectangular, with a flat top, while the nanoislands developed by annealing at temperatures higher than the bulk eutectic temperature have more complex, octagonal shapes. Moreover, the octagonal Au nanoislands are nearly half-buried in the Ge substrate and surrounded by a crystalline Ge rim.